STRATEGI ADAPTASI PETANI PELADANG DAYAK MERATUS DI DESA LOKLAHUNG KECAMATAN LOKSADO KABUPATEN HULU SUNGAI SELATAN - Mila Rismiyati (JURNAL SOCIUS, 2016)
Increasing number of people causing agricultural land increasingly narrow and there are some that are not fertile agricultural land, depletion of nutrients in the soil and there is some land in the Malaris village could not be planted because infertile. Things like this cause Malaris Village community has two strategies, namely (1) adaptation strategies in the areas of estate and (2) adaptation strategies in circular mobility. The purpose of adaptation strategies they do is attempt to struggle to survive and raise living standards.This study uses qualitative research using ethnographic methods. Data collection techniques using observation, interview and documentation. Analysis of data using qualitative data model of Miles and Huberman. The study was conducted in the Loklahung village Loksado district Hulu sungai Selatan. The Loklahung village has four halls (village/cluster houses) are: Malaris, Loa Panggang, Manakili and Manutui. More studies are centered on the Malaris village.The results can be concluded that the adaptation strategies plantations, rubber people occupy an important position in the economy of swidden farmers business: that meet the needs of market goods, while shifting meet the basic needs of its life. Adaptation strategies in circular mobility they do because of the amount to the ever increasing population, land increasingly narrow and there is some land in the Malaris  village could not be planted because infertile.Suggestions from this study are (1) need to enrich and increase the repertoire of knowledge to the development of theories of sociology and anthropology and a source of learning for teaching social studies at the school, and (2) need for a variety of knowledge and skills in the development of new business opportunities.Kata Kunci:  Strategi Adaptasi, Perkebunan, Mobilitas Sirkuler